Contextualized impacts of an infodemic on vaccine hesitancy: The moderating role of socioeconomic and cultural factors. Issue 5 (September 2022) - Lin, Fen; Chen, Xi; Cheng, Edmund W
Highlights: Information overload and misinformation are two different types of infodemic. Information overload decreased while misinformation increased vaccine hesitancy. The older and highly-educated participants were less susceptible to infodemic. High socioeconomic status buffers the negative impacts of infodemic on vaccination. Collectivism and authoritarian mentality ease the negative impacts of infodemic. Sustainable global recovery requires contextualized communication and intervention. Abstract: This study examines how perceived information overload and misinformation affect vaccine hesitancy and how this is moderated by structural and cultural factors. By applying and extending the fundamental cause theory, this study proposes a contextualized impact model to analyze a cross-national survey of 6034 residents in six societies in Asia, Europe and North America in June 2021. The study finds that (1) Older and highly-educated participants were less susceptible to COVID-19 information overload and belief in vaccine misinformation. (2) Perceived information overload led to an increase in vaccine acceptance and uptake, whereas belief in vaccine misinformation caused a decrease. (3) The structural differentiation of vaccine hesitancy was salient and higher socioeconomic status could buffer the negative impact of misinformation on vaccine acceptance. (4) Cultural factors such as collectivism and authoritarian mentality also served as buffers against the misinformation that reduced vaccine acceptance and uptake. These findings add nuanced footnotes to the fundamental causes theory and contribute to the discussion on the global recovery from the infodemic. Besides fact-checking and improving individual information literacy, effective and long-term information management and health policies must pay attention to stratified information gaps across socioeconomic groups, and to contextualize the communication and intervention strategies in different cultures.